Explosive COVID-19 outbreak in a German nursing home and the possible role of the air ventilation system. (December 2022) - Hurraß, J.; Golmohammadi, R.; Bujok, S.; Bork, M.; Thelen, F.; Wagner, P.; Exner, D.; Schönfeld, C.; Hornei, B.; Kampf, G.; Exner, M.
Summary: Background: Most COVID-19 outbreaks in nursing homes are explained by transmission of SARS-CoV-2 from nurses or visitors. Methods and results: We describe an outbreak with 64 of the 67 residents identified as COVID-19 cases within two weeks (34 in nursing block 1, 30 in nursing block 2), at least 32 of them had relevant symptoms of COVID-19. Thirteen of the residents' deaths were associated with COVID-19. In addition, 27 of approximately 60 staff members were identified as COVID-19 cases, 23 of them had relevant symptoms. In none of the samples from residents or staff was a mutation of SARS-CoV-2 detected. Quarantine of the residents was already in force at the beginning of the outbreak. A common source among the staff was considered to be unlikely because the two nursing home blocks had no staff rotation and the staff had to wear FFP2 masks during contact with residents. Three months after the outbreak the RNA of SARS-CoV-2 was detected on 14 of 39 sampled indoor surfaces of the air ventilation system with Ct values between 34.9 and 41.9, but only at the air supply in the corridor (11 of 24 samples) and the air overflow in the door between the corridor and the residents' rooms (three of 11 samples) but not at the air exhaust in the residents' bathrooms. Conclusions: The air ventilation system and an inversion weather situation three days before the first confirmed case may have enhanced viral spread inside the nursing home assuming that a common source with a high viral load had existed at the time of outbreak.